Assesment of Factors Affecting Technical Inefficiency of Manufacturing Industries in Iran - Mohammad Nabi Shahiki Tash; Javad Taherpoor; Elham Shivaii (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2014)
Abstract The main objective of this paper is to measure technical deficiency as well as identifying its effective determinants in 23 active industries at 2-digit level ISIC codes during the period 1995-2009. The paper has applied the technical deficiency criterion based on the Collie and Batis approach using the Translog production function in the industries. The findings indicate that the Iranian manufacturing industries have experienced an increasing trend for efficiency so as we have found an increase in the technical efficiency coefficient for all the manufacturing industries in the investigated period. The highest level of technical deficiency is observed in the following industries: production of garment and production and dying of fur;  publishing, printing and copying of recorded media; manufacturing of textiles; and recycling. On the other hand, the highest level of technical efficiency is found in the manufacturing of chemicals and chemical products. The results show that the average value of technical deficiency is equal to 0.47. Also it is found that the more the concentration coefficient, the greater the level of deficiency. In other words, the industries with more concentrated structure have had more deficiency. Given the model, in the industries that have a larger coefficient for skilled workforce and benefit from the economies of scale, the level of deficiency has reduced. The findings also demonstrate that the expenditures for the research and development have not had a statistically significant effect on the deficiency decrease in the industries.